PENGARUH VARIASI PANJANG BENTANG BALOK PADA STRUKTUR RANGKA PEMIKUL MOMEN KHUSUS TERHADAP TINGKAT LAYAN/KINERJA STRUKTUR - Wardhono, Arie (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Abstract Building structures have manystyles, forms andmodels that becomingseparatephenomenon for civil engineer in analyzing its structure. One is structure configuration with length variation ofbeam. The objection ofthis study is to know theperformance level ofstructure along with its element to the variation ofbeam length to structure ductility, to know the global ductility that reached, and also to get the comparison ofdesign target displacement to actual target displacement for every structure model. Analysis will be conducted by comparing of 7 structures model in 2Dform with length variation ofbeam on Special Moment Resisting Frame design. Seismic force analysis will be done based on static equivalent analysis in seismic zone (WG) of6 as according to regulation ofSNI 03-1726-2002 and ATC-40 and ofFEMA-356 as complement using SAP software 2000 Nonlinear software: